2015
DOI: 10.1371/journal.pone.0128680
|View full text |Cite
|
Sign up to set email alerts
|

A Multifaceted Study of Scedosporium boydii Cell Wall Changes during Germination and Identification of GPI-Anchored Proteins

Abstract: Scedosporium boydii is a pathogenic filamentous fungus that causes a wide range of human infections, notably respiratory infections in patients with cystic fibrosis. The development of new therapeutic strategies targeting S. boydii necessitates a better understanding of the physiology of this fungus and the identification of new molecular targets. In this work, we studied the conidium-to-germ tube transition using a variety of techniques including scanning and transmission electron microscopy, atomic force mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 89 publications
1
12
0
Order By: Relevance
“…This smooth surface is also observed on accessory conidia of Aspergillus terreus , whereas phialidic conidium had a striated surface ( Deak et al 2011 ). In S. boydii ( Ghamrawi et al 2015 ), as observed for S. minutisporum and S. aurantiacum , germination primarily occurs at the centre of conidia, and not at the conidial bottom, as observed in S. apiospermum (in the present study and Stepanova et al 2016 ).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…This smooth surface is also observed on accessory conidia of Aspergillus terreus , whereas phialidic conidium had a striated surface ( Deak et al 2011 ). In S. boydii ( Ghamrawi et al 2015 ), as observed for S. minutisporum and S. aurantiacum , germination primarily occurs at the centre of conidia, and not at the conidial bottom, as observed in S. apiospermum (in the present study and Stepanova et al 2016 ).…”
Section: Resultssupporting
confidence: 75%
“…3 ) in all observed cells ( Table I ). Similarly, Ghamrawi et al (2014) , Ghamrawi et al (2015) observed the binding of WGA just on the basis of the conidium of S. boydii , a region where releases scar is present, and along the whole germination extension. Since the polymerisation of N -acetylglucosamine forms the polysaccharide chitin, we hypothesised that the labelling in the full length of germination is due to the chitin synthesis occurring at the site, as a result of apical cell growth.…”
Section: Resultsmentioning
confidence: 79%
“… Yanagita (1963) found that, after the germination of A. niger conidia had started, the incorporation of 14 CO 2 proceeded actively without any lag, and macromolecular substances, such as nucleic acids and proteins, were labeled very rapidly. The importance of 5% CO 2 during the conidial germination process in S. apiospermum , S. aurantiacum , S. boydii , S. minutisporum and L. prolificans is corroborated by studies done by other authors, who analysed conidial germination in L. prolificans ( Meletiadis et al 2001 ), S. apiospermum and S. boydii ( Pinto et al 2004 , Santos et al 2009 , Lopes et al 2010 , Ghamrawi et al 2015 ) after incubation at both room temperature and 37ºC under environmental atmospheric concentration of CO 2 . In all those works, the authors found low percentages of germinated conidia.…”
Section: Resultsmentioning
confidence: 58%
“…In A. fumigatus , the germination of conidia started after 5 h of incubation in the five nutrient media (AM3, YNB, Sabouraud, RPMI alone and RPMI with 2% glucose), although it was delayed by 1.5 h in YNB medium ( Meletiadis et al 2001 ). Ghamrawi et al (2015) found around 30% of germinated conidia in S. boydii after incubation in yeast peptone dextrose for 4 h at 37ºC in atmospheric concentration of CO 2 . All these controversial results, including our own findings, could be explained due to the employment of different growth conditions such as culture medium composition and CO 2 concentration, which are two relevant parameters that modulate the differentiation process in several fungi ( Allen 1965 , D’Enfert 1997 , Osherov & May 2001 , Wächtler et al 2012 , Gilmore et al 2013) .…”
Section: Resultsmentioning
confidence: 95%
“…However, we showed previously that this enzyme is a glycosyl phosphatidyl inositol-anchored cell wall protein expressed exclusively at the surface of the conidia which are the infecting form of the fungus. 43 Likewise, four SOD genes were identified in A. fumigatus genome, two of them were highly expressed in conidia while AfSOD3 was expressed only in hyphae. 44 Finally, since macrophages are less involved in the immune response against hyphae than neutrophils, our model could explain that a higher number of genes were modulated when 24h-old hyphae of S. apiospermum were exposed to neutrophils (13 genes overexpressed vs. only four with macrophages).…”
Section: Discussionmentioning
confidence: 99%